Optimizing the Use of Water, Energy and Waste Resources in Green Buildings: Critical Review, Benefits and Challenges - Firman Sarifudin; Jin, Oei Fuk (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
Research on themes related to green buildings is very important because it relates to building environmentally friendly buildings that prioritize sustainability. However, Green Building and Sustainable Development Goals (SDGs) research tends not to be comprehensive because it only relates to building construction and energy efficiency. For this reason, this research will discuss various things about green buildings and criticize what has been analyzed, whether it is still appropriate or not, considering current conditions that already use wireless and IoT technology. Through literature review techniques, this research examines themes related to the civil sector and the implementation of Green Building goals and SDGs. The Systematic Literature Review (SLR ) method is used. Namely, in-depth criticism and evaluation of previous research carried out systematically by applying applicable standards, using the Viosviewer and Publish and Perish applications. This method examines research results published in journals in a particular field. Literature reviews discuss previous research that meets SDGS objectives and is related to the civil sector. This research used 300 earlier studies with a research period ranging from 2010-2023 or 14 years. The research results show that the theme that is often raised is green materials and technology. The use of technology to measure building performance and energy efficiency is the most widely discussed theme. However, the analysis of Green Building and SDGs is rarely linked to IoT technology, saving water use, rainwater utilization, environmentally based wastewater management, and green building education, even though this is closely related to cost efficiency, energy efficiency, and speed, in communicating to achieve SDGs goals.